2020
DOI: 10.1186/s12943-020-01246-x
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA inhibits DNA damage repair by interacting with host gene

Abstract: Background: Deregulated circular RNAs (circRNAs) are associated with the development of cancer and therapy resistance. However, functional research of circRNAs mostly focus on potential miRNA or protein binding and more potential regulation of circRNA on host gene DNA in cancers are yet to be inspected. Method: We performed total RNA sequencing on clinical breast cancer samples and identified the expression patterns of circRNAs and corresponding host genes in patient blood, tumor and adjacent normal tissues. q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(197 citation statements)
references
References 48 publications
2
170
0
Order By: Relevance
“…Given the cytoplasmic localization and exonic formation of circRSU1, as well as the opposite expression trend of circRSU1 and linear mRSU1 under IL-1β and H 2 O 2 stimulation, we hypothesized the presence of a mechanism that regulates their biogenesis. Xu et al 86 reported that circSMARCA5 can form an R-loop at its parent gene locus, which results in transcriptional pausing of SMARCA5 and leads to the upregulated circSMARCA5 and downregulated mSMARCA5 in breast cancer. Zhang et al 87 also reported a mechanism for the selection of RNA pairing across flanking introns or within a single individual intron that leads to competition between the back-splicing of circRNAs and the canonical splicing of linear mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the cytoplasmic localization and exonic formation of circRSU1, as well as the opposite expression trend of circRSU1 and linear mRSU1 under IL-1β and H 2 O 2 stimulation, we hypothesized the presence of a mechanism that regulates their biogenesis. Xu et al 86 reported that circSMARCA5 can form an R-loop at its parent gene locus, which results in transcriptional pausing of SMARCA5 and leads to the upregulated circSMARCA5 and downregulated mSMARCA5 in breast cancer. Zhang et al 87 also reported a mechanism for the selection of RNA pairing across flanking introns or within a single individual intron that leads to competition between the back-splicing of circRNAs and the canonical splicing of linear mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hsa_circ_0025202 could absorb miR-182-5p to regulate the expression and activity of FOXO3a and then affect tumor inhibition and tamoxifen sensitization effects, indicating that hsa_circ_0025202 could be a therapeutic target in patients with HR-positive BC, especially in those receiving TAM therapy. In contrast to its host gene SMARCA5, circSMARCA5 is reduced in breast cancer tissues [ 74 ]. The enforced expression of circSMARCA5 could induce drug sensitivity in breast cancer cell lines in vitro and in vivo.…”
Section: The Characteristics and Categories Of Circrnasmentioning
confidence: 99%
“…circKIAA1429 accelerated hepatocellular carcinoma advancement through enhancing ZEB1 mRNA stability [26]. circSMARCA5 terminated the transcription of SMARCA5 to inhibit DNA damage repair [14]. circSHPRH suppressed glioma tumorigenesis by encoding a novel protein [36].…”
Section: Circmettl3 Is Upregulated In a M6a-dependent Mannermentioning
confidence: 99%
“…Previous studies showed circRNAs might act as a sponge to increase its host gene expression [39][40][41] or decrease the parental gene expression by terminating the transcription of the parental gene [14]. However, the relation of circMETTL3 and its parental gene, METTL3, was still elusive.…”
Section: Circmettl3 Is Upregulated In a M6a-dependent Mannermentioning
confidence: 99%